Anticentromere antibody in primary biliary cirrhosis. Issue 6 (December 1982) - Bernstein, R M; Callender, M E; Neuberger, J M; Hughes, G R; Williams, R
Abstract : An autoantibody specific for the centromere region of chromosomes and recently detected in the serum of patients with scleroderma was found in ther serum of 10 (9.1%) of 110 consecutive patients presenting with primary biliary cirrhosis. It was found exclusively among those with scleroderma, giving a prevalence of 50% in that group, and all patients with telangiectasia or calcinosis had the antibody. It was not found in 80 patients with chronic active hepatitis, including the 'autoimmune' variety. The pathogenetic significance of anticentromere antibody is not yet established, but this study confirms its specificity for scleroderma in the context of primary biliary cirrhosis.